1997
DOI: 10.1002/(sici)1099-0518(19970915)35:12<2371::aid-pola6>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of well‐defined polychlorostyrenes by living radical polymerization with 4‐methoxy‐2,2,6,6‐tetramethylpiperidine‐1‐oxyl

Abstract: Radical polymerization of 2-, 3-, and 4-chlorostyrenes (ClSts) was investigated with benzoyl peroxide (BPO) as an initiator, in the presence of 4-methoxy-2,2,6,6-tetramethylpiperidine-1-oxyl (MTEMPO). The polymerization was performed in bulk for 3.5 h at 95ЊC and then continued for a defined time at 125ЊC to give the corresponding poly(ClSt)s with narrow polydispersity in high yield. It was found that the polymerization proceeded in accordance with a living mechanism in all cases, because the molecular weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Electron-withdrawing styrene substituents were found to increase CRP rate in the presence of TEMPO [27] and 4-methoxy-TEMPO (MTEMPO). [28] Similarly, CRP of p-styrene sulfonate was found to occur at a much higher rate than styrene. [29] A study on CRP of methylstyrenes in the presence of MTEMPO indicated that polymerisation of the o-isomer was the most rapid due to steric hindrance.…”
Section: Fullmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron-withdrawing styrene substituents were found to increase CRP rate in the presence of TEMPO [27] and 4-methoxy-TEMPO (MTEMPO). [28] Similarly, CRP of p-styrene sulfonate was found to occur at a much higher rate than styrene. [29] A study on CRP of methylstyrenes in the presence of MTEMPO indicated that polymerisation of the o-isomer was the most rapid due to steric hindrance.…”
Section: Fullmentioning
confidence: 99%
“…The rate of TEMPO-mediated CRP of substituted styrenes was found to be greatest with monomers bearing electron-withdrawing substituents. [27][28][29] The phosphonato-substituted nitroxides reported by Tordo et al [12] are reported to give faster polymerisations than TEMPO due to the electron withdrawing influence of the phosphonate group. Presumably, the results in these cases are due to weakening of the alkoxyamine C1O bond by a negative inductive effect.…”
Section: Nitroxide Synthesis and Use In Polymerisationsmentioning
confidence: 99%
“…Whereas this polymer could be quantitatively obtained by the reaction of a living cationic PTHF and sodium 4-oxy-TEMPO, the TEMPO-supported PTHF acted as a polymeric counter radical for living radical polymerization of styrene, giving the poly(THF- block -styrene) in quantitative efficiency. The development of the method of this quantitative synthesis of the block copolymer has been based on numerous results, obtained by many investigators, concerning the styrene polymerization using TEMPO. Our recent results can be included among this research. In this recent study, it was found that the concentration of the growing polymer chain was identical to the initial concentration of TEMPO, with the result that all the polystyrenes obtained had the aminoxy moiety at their terminals …”
Section: Introductionmentioning
confidence: 93%
“…Styrene is the most studied monomer in NMLFRP (29,57,(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74). The kinetics and mechanism of this process have been disclosed by Veregin et al (64).…”
Section: Substituent Effect On Nitroxide-mediated Living Free-radicalmentioning
confidence: 99%